Analysis of fatty acids and sex steroid hormones in rainbow trout testes (Oncorhynchus mykiss) during the reproductive process. (9th June 2022) - Bhat, Rayees Ahmad; Saini, Sudha; Saoca, Concetta; Maricchiolo, Giulia; Fazio, Francesco
Abstract: In the present study, we aimed to examine the cellular structure of the testes, the hormonal changes occurring throughout the reproductive cycle, and the fatty acid composition in rainbow trout. An electron microscopic analysis was conducted to investigate the morphology and cellular changes during the development of the testes. Germ cells were observed in different stages of differentiation: primary spermatogonia (PSGs), secondary spermatogonia (SSGs), primary spermatocytes (PSCs), secondary spermatocytes (SSCs), spermatids (SPDs) and spermatozoa (SZs). Differentiated spermatozoa were observed within the cysts. Regarding steroid hormones, the maximum level of testosterone was in the mature stage, and the minimum level was in the spent stage; for 11‐ketotestosterone, the highest level was in the maturing stage and the lowest level was in the spent stage. In terms of the fatty acid composition, the levels of C14, C15, C16, C18, C16:1n7, C18:1n7, C18:1n9, C20:4n6, n‐3 PUFAs, n‐6 PUFAs, C20:5n‐3 (EPA), C22:5n‐3 (DPA) and C22:6n3 (DHA) (g −1 of gonad wet weight) were the lowest during the immature stage and the highest during the mature stage of the testes. The major significance of the study is the sex steroid hormonal profile, the primary regulators of spermatogenesis and the fatty acid composition, which is important for the development of gonads and sperm. These data should contribute to the knowledge regarding the reproductive biology of male rainbow trout, for which research data remain scarce.